The long-term evolution of neutron star merger remnants – II. Radioactively powered transients. Issue 1 (31st January 2014) - Grossman, Doron; Korobkin, Oleg; Rosswog, Stephan; Piran, Tsvi
Abstract: We use 3D hydrodynamic simulations of the long-term evolution of neutron star merger ejecta to predict the light curves of electromagnetic transients that are powered by the decay of freshly produced r -process nuclei. For the dynamic ejecta that are launched by tidal and hydrodynamic interaction, we adopt grey opacities of 10 cm 2 g −1, as suggested by recent studies. For our reference case of a 1.3–1.4 M_ merger, we find a broad IR peak 2–4 d after the merger. The peak luminosity is ≈2 × 10 40 erg s −1 for an average orientation, but increased by up to a factor of 4 for more favourable binary parameters and viewing angles. These signals are rather weak and hardly detectable within the large error box (∼100 deg 2 ) of a gravitational wave trigger. A second electromagnetic transient results from neutrino-driven winds. These winds produce 'weak' r -process material with 50 < A < 130 and abundance patterns that vary substantially between different merger cases. For an adopted opacity of 1 cm 2 g −1, the resulting transients peak in the UV/optical about 6 h after the merger with a luminosity of ≈10 41 erg s −1 (for a wind of 0.01 M_ ) These signals are marginally detectable in deep follow-up searches (e.g. using Hypersuprime camera on Subaru). A subsequent detection of the weaker but longer lasting IR signal would allow an identification of the merger event. We briefly discuss the implications of our results to the recent detection of a near infrared (nIR) transient accompanying GRB 130603B.